Analysis of Outdoor Advertising Visual Pollution Using Analytical Hierarchy Process in Semarang City (Case Study: Tugu Muda Semarang Area) - Nisa, Afifatun; WIjaya, Arwan Putra; Yusuf, Muhammad Adnan (Universitas Negeri Semarang, 2024)
This study aims to determine the visual pollution of outdoor advertising in Semarang City, especially in the city center, namely Tugu Muda with five road segments supporting the area. The method used is the Analytical Hierarchy Process (AHP) by considering six parameters including physical conditions, land use, placement, display surface, size, and distance. The data used are spatial data in the form of taking coordinates in the field using the Survey123 application and non-spatial data in the form of accumulated scores for each parameter used. The results of this study are that the surface display parameter has the highest weight of 38.127%. 209 points of outdoor advertising have been surveyed in the field with a total of 85 points of low visual pollution, 52 points of high visual pollution, 37 points of medium visual pollution, and 20 and 15 points of very low and very high visual pollution respectively. Although the distribution of outdoor advertising has a fairly high density, the results of processing and scoring with the AHP method of outdoor advertising with low visual pollution dominate.